I know better: Self-esteem, egocentrism, and policy learning in the liberalization of Belgian network industries - Stéphane Moyson (International Review of Public Policy)
Policy learning is a key mechanism of policy change through which policy actors revise their beliefs and preferences over time as a result of social interactions and new information. The individual psychology of policy actors is crucial to understanding how institutional settings and social practices influence policy learning. This article looks at the effects of self-esteem—i.e., how policy actors value themselves—and egocentrism—i.e., their tendency to confuse their subjective perceptions with objective reality and to disqualify the perceptions of others.Based on regression analyses of a 2012 survey of 255 Belgian policy actors who had been involved in the European liberalization process of the rail and electricity sectors, the findings suggest that policy actors who score higher on self-esteem or egocentrism feel that they “know better”: they align their policy preferences to new policy information less than policy actors who score lower. Only egocentrism directly leads to a negative adjustment of policy actors’ preferences towards liberalization policies over time. The theoretical and practical implications of these findings are discussed. They shed light on policy actors’ modes of reasoning and are thus an important step in the research agenda on “learning governance”.